Harvest Control Rules of Multispecies Scads (Decapterus spp.) Fishery in Blitar Waters, East Java - Ledhyane Ika Harlyan; Shobriyyah Afifah Nabilah; Daduk Setyohadi; Muhammad Arif Rahman; Supapong Pattarapongpan (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research • The feedback harvest control rule resulted in the lowest allowable biological catch estimation than the surplus production models. • The feedback harvest control rule adapted the recent years of historical catch data. • The surplus production models might result in over or under catch estimation, not considering the recent data. • This multispecies fishery could not provide species specific data as surplus production models required; therefore, it might be better to use the feedback harvest control rule that has been validated for multispecies fisheries.